Study of genotype X environment interactions and agro-technological behavior of durum wheat varieties applied in different agro-climatic zones of Algeria - Hacini, Nesrine; Djelloul, Radia; Desclaux, Dominique (PLANT ARCHIVES, 2022)
Cereals occupy an essential place in agricultural research programs on a global scale. In Algeria, this place is all the most important as the country wants to achieve stable production of cereals, in particular durum wheat and common wheat. However, Algerian cereal farming remains very dependent on climatic conditions and is subject to very frequent droughts. Focusing on the cereal production under conditions of water deficit, many studies have shown that cereals have mechanisms of resistance to environmental constraints favoring their growth, development, and grain yield. The present work is interested in the study of some mechanisms of resistance to drought which seem to be among the most important in the production of cereals in Algeria. The knowledge of the intra-specific variability that plants manifest for tolerance to water stress allows considering the selection of resistant genotypes. This is why several agronomic criteria (components of yields) were used through a few sufficiently simple and rapid tests in order to discriminate between genotypes for resistance to water stress in the three different climatic stages.